High-light-inducible proteins control associations between chlorophyll synthase and the Photosystem II biogenesis factor Ycf39 - Wysocka, Anna; Kulik, Natalia; Shukla, Mahendra K; Opatíková, Monika; Kouřil, Roman; Jackson, Philip J; Brindley, Amanda A; Janouškovec, Jan; Kiss, Éva; Hitchcock, Andrew; Komenda, Josef; Hunter, C Neil; et al. (Plant physiology, 2025)
The biogenesis of Photosystem II is a complicated process requiring numerous auxiliary factors to assist in all steps of its assembly. The cyanobacterial protein Ycf39 forms a stress-induced complex with 2 small chlorophyll-binding, High-light-inducible proteins C and D (HliC and HliD), and has been reported to participate in the insertion of chlorophyll molecules into the central D1 subunit of Photosystem II. However, how this process is organized remains unknown. Here, we show that Ycf39 and both HliC and HliD can form distinct complexes with chlorophyll synthase (ChlG) in the model cyanobacterium Synechocystis sp. PCC 6803. We isolated and characterized ChlG complexes from various strains grown under different conditions and provide a mechanistic view of the docking of Ycf39 to ChlG via HliD and the structural role of HliC. In the absence of stress, chlorophyll is produced by the ChlG-HliD2-ChlG complex, which is stabilized by chlorophyll and zeaxanthin molecules bound to the HliD homodimer. The switch to high light leads to stress pressure and greatly elevated synthesis of HliC, resulting in the replacement of HliD homodimers with HliC-HliD heterodimers. Unlike HliD, HliC cannot interact directly with ChlG or Ycf39. Therefore, the original ChlG-HliD2-ChlG complex is converted into a ChlG-HliD-HliC hetero-trimer that presumably binds transiently to Ycf39 and the nascent D1 polypeptide. We speculate that this molecular machinery promotes the delivery of chlorophyll to D1 upon high-light-induced chlorophyll deficiency. The HliD homodimers formed under standard, nonstress growth conditions and attached to ChlG could serve as an emergency chlorophyll reserve.
Keywords: bakteriální proteiny; ligasy tvořící vazby C-O; Photosystem II Protein Complex; světlo; Synechocystis; Chlorophyll; chlorofyl; Carbon-Oxygen Ligases; Light-Harvesting Protein Complexes; světlosběrné proteinové komplexy; Light; Bacterial Proteins; fotosystém II (proteinový komplex)